Establishment of the Causal Agent(s) of Spike Shedding and Stem Wilting of Pepper (Piper nigrum L.) in Morogoro District, Tanzania - Abdul J. Shango; Ramadhani O. Majubwa; Amon P. Maerere (Advances in Agriculture)
Pepper (Piper nigrum L.) serves as a source of income to smallholder spice farmers in Morogoro district of Tanzania. Recently, spike shedding and stem wilting of pepper plants were reported to cause about 30% yield loss of the crop. This study was undertaken to identify the causal agent(s) of the problems. Three pepper gardens in each of the four hamlets (Nyange, Doga, Tandai, and Lukenge) in Tandai village (Kinole ward) were surveyed, and plant tissue and soil samples were collected for laboratory analysis. An experiment was laid out in a randomized complete block design with three replications. Pepper cultivars, Babu kubwa, Babu ndogo, Babu kati, and Ismailia grown in the study area, were used as treatments for evaluation of the prevalence of spike shedding and stem wilting. Treatments mean separation was conducted based on Duncan’s multiple range test at p=0.05. Regression (R2) and simple correlation (r) analyses between stem wilting (incidence and severity) and termite pest infestation were performed. The identified pathogen in most of the soil and plant tissue samples was Fusarium oxysporum. The nutrients, N, P, Mg, and Cu, concentration in soil and leaf samples was below the optimal ranges. Termite attacks were significantly high in some farmer’s gardens where up to 50.5% of the pepper plants was damaged. Hence, a significant positive correlation was observed between termite pest infestation in gardens and both incidence (r = 0.881, R2 = 0.74, p<0.001) and severity of stem wilting (r = 0.918, R2 = 0.84, p<0.001) of pepper plants. Most of the termite attacks and damages (70%) were observed on pepper plants supported on silver oak, unlike those trained on Jatropha. A higher percentage of undeveloped berries (36%) and intermediate-size berries (34%) was recorded on cultivars “Babu kati” and “Babu kubwa,” respectively. Multiple factors have been associated to be the causes of spike shedding and stem wilting of pepper, which could be used to develop appropriate control solutions useful to farmers. Confirmation of F. oxysporum pathogenicity is recommended. A comprehensive study is suggested on the repellent or lethal activities of Jatropha against F. oxysporum and termites. Furthermore, studies through field experiments are needed to generate site-specific soil nutrient improvement recommendations and design an integrated approach to control F. oxysporum and termites and to determine existing alternative host plants for these pests.